2007
DOI: 10.1149/1.2780941
|View full text |Cite
|
Sign up to set email alerts
|

Study on Degradation of the Pt-Ru Anode of PEFC for Residential Application (2): Analyses of the MEAs Degraded in the Anode Performance

Abstract: Significant decrease in the voltage and increase in H 2 gain were observed after the low current density operation. However, recovery in voltage and decrease in H 2 gain were also observed by the dry treatment. The impedance of degraded MEA just after the low current density operation increased at the low frequency region in CO(10ppm)/H 2 (balance). On the other hand, the impedance of MEA that the H 2 gain was increased by long term operation for more than 20,000 h was increased at higher frequency region in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…It has been also reported that flooding of the anode increases the local concentration of CO in the micropores of the anode, and greatly enhances CO-poisoning at the anode (20). The sudden drop of CO tolerance shown in Fig.…”
Section: Loss Of Co-tolerance Of Pt-ru Alloy Anode Catalystmentioning
confidence: 82%
“…It has been also reported that flooding of the anode increases the local concentration of CO in the micropores of the anode, and greatly enhances CO-poisoning at the anode (20). The sudden drop of CO tolerance shown in Fig.…”
Section: Loss Of Co-tolerance Of Pt-ru Alloy Anode Catalystmentioning
confidence: 82%
“…1 (b), is well agreed with the calculated resistance using Eq. [2] at higher H 2 concentration, but much higher than the calculation at lower H 2 concentration. This discrepancy might be caused by actual diffusion control due to low H 2 concentration.…”
Section: Resultsmentioning
confidence: 52%
“…Therefore, if pure H 2 is used as fuel gas, E is independent of U f , and so the second impedance in Eq. [2] doesn't appear. On the other hand, at low U f or under so called "differential cell" conditions, both f U E ∂ ∂ / and i U f ∂ ∂ / become small, therefore, the second impedance is also negligible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the fundamental researches, it was found that the anode potential shifted to 0.8 V vs. RHE at a local area by the inhomogeneous composition of gas on the cathode while the H 2 was feed to anode continuously 1) , and Ru around the surface area of catalyst disappeared by hundreds of thousands times potential cycling in the potential range 0.05 ~ 0.4 V vs. RHE 2) . In addition, it was clarified that the flooding in the anode affected the CO tolerance performance 3) . And, the quantitative model of CO poisoning characteristic was proposed 4) .…”
Section: Introductionmentioning
confidence: 99%